Sundry papers...collected Anno Domini 1774 - Aubarede, Marquis d'; Brown, Mountfort; Collett, J. A.; Saint Pierre, Louis de, active 1772.
One volume (93 pages) containing miscellaneous papers, collected in 1774, including two treatises by Louis de Saint-Pierre on the cultivation of grapes, silk, indigo, and fruit trees in North America and particularly in the New Bordeaux colony in South Carolina; copies of a land grant and indenture between King James II and William Penn, Sr.; a brief history of Anson County, N.C. by J.A. Collett; account of a land sale on the Isle St. John (now Prince Edward Island); a plan of Mexican commerce; a statement of the reasons for a civil government in the British dominions adjoining the Mississippi River by Mountfort Brown, governor of West Florida; and proposals of the Marquis D'Aubarede concerning the settlement of the Mississippi River valley.
Transcripts.
Collection material in English.
Keywords: James -- II, -- King of England, -- 1633-1701.; Penn, William, -- 1644-1718.; Agriculture -- South Carolina; Fruit trees -- North America; Indigo; Silk industry -- North America; Viticulture -- North America; Anson County (N.C.) -- History; Bordeaux (S.C.); Florida -- History -- English colony, 1763-1784.; Mexico -- Commerce; Mississippi River Valley -- History; Prince Edward Island